2015
DOI: 10.1039/c5ra03432a
|View full text |Cite|
|
Sign up to set email alerts
|

Ball flower like manganese, strontium substituted hydroxyapatite/cerium oxide dual coatings on the AZ91 Mg alloy with improved bioactive and corrosion resistance properties for implant applications

Abstract: Bio-degradable metals and alloys have been suggested as revolutionary potential materials for bone-related treatment. Of these materials, the AZ91 magnesium alloy (AZ91 Mg alloy) emerges as an attractive candidate due to its non-toxicity and outstanding mechanical properties. Even though magnesium alloys are widely studied as orthopedic implants for bone replacement and bone regeneration, their undesirable rapid corrosion rate under physiological conditions has limited their actual clinical applications. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 56 publications
(104 reference statements)
0
11
0
Order By: Relevance
“…Furthermore, the inclusion of a mineral ion with bioactive property into HA nanoparticles might enhance the biological properties of the implants . In particular, the beneficial effect of different bioactive ions such as Sr 2+ , Ba 2+ , Mg 2+ , and Zn 2+ for substitution into pure HA was reported by Gopi et al Recent studies focus on the substitution with dual minerals in calcium apatite for many biological and medical applications. As a bioactive element, Sr 2+ (a trace element in the human bone) is a suitable candidate for the treatment of osteoporosis along with improving the bone strength of the implant .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the inclusion of a mineral ion with bioactive property into HA nanoparticles might enhance the biological properties of the implants . In particular, the beneficial effect of different bioactive ions such as Sr 2+ , Ba 2+ , Mg 2+ , and Zn 2+ for substitution into pure HA was reported by Gopi et al Recent studies focus on the substitution with dual minerals in calcium apatite for many biological and medical applications. As a bioactive element, Sr 2+ (a trace element in the human bone) is a suitable candidate for the treatment of osteoporosis along with improving the bone strength of the implant .…”
Section: Introductionmentioning
confidence: 99%
“…99 Another application is that the CeO 2 and HA composites attach to other materials with specific mechanical stability, such as AZ91 Mg alloy. 100 Researchers developed manganese (Mn), and strontium (Sr) substituted hydroxyapatite (Mn, Sr-HAP) coatings on the CeO 2 coated AZ91 Mg alloy, which enhanced the corrosion resistance of the whole material to facilitate the clinical application of AZ91 Mg alloy. Sanyal et al 101 prepared ceria-stabilized zirconia (CSZ) in fluorohydroxyapatite (FHA) by the sol-gel method.…”
Section: Osteosarcomamentioning
confidence: 99%
“…Besides biocompatibility and osteoinductive activity, corrosion of implant material is one of the main concerns from the biomedical perspective. For instance, Gopi et al [17] studied the corrosion performance of Sr doped HaP coatings with non-doped HaP coatings and showed that Sr doped HaP coatings exhibited lower corrosion current density. Haung et al [18,19] investigated the corrosion behavior of Sr doped HaP coatings and attributed the higher corrosion resistance to the dense nature and smaller crystallite size of the coatings.…”
Section: Introductionmentioning
confidence: 99%